Delegation-based conversion from CPA to CCA-secure predicate encryption. (3rd May 2020) - Nandi, Mridul; Pandit, Tapas
In 2011, Yamada et al. proposed CPA to CCA-secure conversions for attribute-based encryption (ABE) based on the properties, verifiability and delegation. Later, the verifiability-based conversion was generalised from ABE to predicate encryption (PE) by Yamada et al. (2012) and Nandi et al. (2017). We observe that for bilinear-pairing based PE schemes, the cost of CCA-decryption blows up to the double of the cost of CPA-decryption due to verifiability testing. Therefore, the conversion based on delegation is mostly acceptable whenever a delegation-based conversion is available for the primitive PE scheme. In this paper, we investigate a generic delegation-based conversion from CPA to CCA-secure predicate encryption schemes. Our conversion generalises the delegation-based conversion of Yamada et al. (2011) from ABE to PE. We show that our conversion captures many subclasses of PE, e.g., (hierarchical) inner-product encryption, (doubly-)spatial encryption and functional encryption for regular languages.